Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1186/s12877-022-03302-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of multicomponent exercise in cognitive impairment: a systematic review and meta-analysis

Abstract: Background Multicomponent physical exercise is the most recommended type of physical intervention in older adults. Experimental data suggest the relevance of the muscle-brain axis and the relationship between muscle contraction and release of brain-derived neurotrophic factor, however, the impact of this relationship on cognition remains unclear, especially in people with diagnosis of cognitive impairment. This study assesses the effect of multicomponent physical exercise on global cognition in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 50 publications
1
21
0
Order By: Relevance
“…Especially appealing may be the potential benefits of the Vivifrail MCE program on the cognitive domain of older adults with mild cognitive impairment (MCI). Despite previous research has shown that exercise might be an effective intervention to cognition in healthy older adult populations [ 30 ], so far, its effectiveness in MCI/dementia populations is less clear [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…Especially appealing may be the potential benefits of the Vivifrail MCE program on the cognitive domain of older adults with mild cognitive impairment (MCI). Despite previous research has shown that exercise might be an effective intervention to cognition in healthy older adult populations [ 30 ], so far, its effectiveness in MCI/dementia populations is less clear [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, we suggest that the community and families should work together to develop appropriate exercise programs, such as tai chi, baduanjin, qigong, and yoga, to improve sleep quality and cognitive function among older adults with T2DM. A comprehensive exercise program not only offers a variety of pleasurable activities to alleviate depression, it can also improve motor and cognitive performance by providing multiple stimulation of thought, attention, and memory, 60 which can be more beneficial than a single cognitive or exercise program. We also found that high levels of sleep quality were associated with lower depressive symptoms and lower risk of developing COI.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Chen et al, reported that exercise training can have a positive effect on cognition and executive function in elderly, but the effect may differ depending on the age of the elderly [ 39 ]. In addition, considering that the upregulation of neurotrophic factors through exercise training can benefit the cognitive function of the elderly [ 40 , 41 ], it is suggested that further studies need to verify changes in cognitive function.…”
Section: Discussionmentioning
confidence: 99%